Character Education E-Module Based on the Local Jambi Figure Colonel Abundjani to Enhance Students’ Nationalism - Hendra; Anny Wahyuni (Universitas Pendidikan Ganesha, 2026)
This research is motivated by the decline in nationalism among the younger generation due to globalization and the lack of innovation in character education. This study aims to develop and test the effectiveness of a local figure-based character education e-module as a means of improving students' nationalism. The type of research used is research and development with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects involved material experts, design experts, and students as product users. Data collection was carried out through interviews, documentation, and questionnaires, with instruments in the form of validation sheets, response questionnaires, and nationalism attitude questionnaires. Data analysis used qualitative and quantitative descriptive approaches to assess the feasibility and effectiveness of the product. The results of the study indicate that the developed e-module has a very good level of feasibility in terms of material and design aspects, and received positive responses from users. In addition, the use of the e-module has been proven to significantly improve students' nationalism attitudes. The conclusion of this study confirms that the local figure-based e-module is effective as a contextual and meaningful character learning medium. The implications of this research indicate that the development of teaching materials based on character values can be an alternative strategy in strengthening educational character, while simultaneously encouraging learning that is more reflective, independent, and oriented towards strengthening national identity.